Pelaksanaan Menyusui pada Ibu yang Terkonfirmasi Positif Covid-19 - Ethic Palupi; Santahana Febrianti; Ardiyan Ida Kusumawati; Estri Murwati; Khristanti Puji Lestari; Kristina Eka Purwanti (FORIKES, 2022)
Covid-19 is continuing to spread around the world, Indonesia is one among those that is affected. It is infecting everyone, including pregnant women. There are 536 pregnant women affected by Covid-19 and 51.9% without symptoms. The anxiety of mothers with confirmed Covid-19 arises when they will breastfeed the baby and the risk of transmission because of close contact can interfere with mothers’ psychology. The objective of the study is to know the implementation of breastfeeding in mothers with confirmed Covid-19. It was a literature review study. The data was searched through Google Scholar database, PubMed, Nursing Journal, Cochranelibrary, with keywords